2019
DOI: 10.1016/j.jff.2019.02.045
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation and stability of a phenolic-rich extract from mango peel within water-in-oil-in-water emulsions

Abstract: Està subjecte a una llicència de Reconeixement-NoComercial-SenseObraDerivada 3.0 de Creative Commons

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 58 publications
2
37
0
1
Order By: Relevance
“…Several studies on encapsulation and delivery of polyphenols have been published in recent years [ 6 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The use of encapsulated polyphenols present in phenolic-rich extracts (e.g., green tea, mango peel, olive leaf or grape seed [ 27 , 28 , 29 , 30 , 31 ]) instead of free molecules improves both the stability and bioavailability of the molecules in vitro and in vivo [ 32 , 33 ] using single and multiple emulsions and nanoemulsions.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on encapsulation and delivery of polyphenols have been published in recent years [ 6 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The use of encapsulated polyphenols present in phenolic-rich extracts (e.g., green tea, mango peel, olive leaf or grape seed [ 27 , 28 , 29 , 30 , 31 ]) instead of free molecules improves both the stability and bioavailability of the molecules in vitro and in vivo [ 32 , 33 ] using single and multiple emulsions and nanoemulsions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that phenolic-rich extracts from mango peel can be successfully encapsulated using long-term stable double emulsions systems 12 . Double emulsions can encapsulate PC from mango peel within the internal aqueous phase (W 1 ) of emulsions, being surrounded by an oil droplet (O) that separates them from a second aqueous phase (W 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The phenolic profile was analyzed in a UHPLC apparatus (Acquity, Waters, Milford, MA, USA) equipped with a diode array detector, as previously reported (Velderrain‐Rodríguez et al, 2019). Separation was performed on a BEH C18 column (1.7 µm, 3.0 × 100 mm) under temperature‐controlled conditions (60°C).…”
Section: Methodsmentioning
confidence: 99%